Why Is There I Rather Than It? Ontology of the Subject in the Upaniṣads - Kudelska, Marta (Studies in Philosophy, History of Ideas and Modern Societies, 2021)
The book explores one of the most important problems in Indian philosophical thought: the subject in its particular relation to the world. In what sense does the subject exist? How does it constitute the world? The analysis hinges on Sanskrit sources, mainly the Upanis. ads. However, it goes beyond the question of the subject. The book discusses the concept of how the subject establishes the world, which - in this cognitive perspective - becomes simultaneously recognised and deformed. Overcoming these deformations becomes a specific soteriological path.